Staphylococcus aureus as a signature species of skin microbiome in actinic keratosis and squamous cell carcinoma: A narrative review - Nilay Duman; Göktürk Oraloğlu; Deniz Ece; Ayse Caner (Dermatologica Sinica)
Cutaneous squamous cell carcinoma (cSCC) is a common type of skin cancer and the second most common type of nonmelanoma skin cancer. Actinic keratosis (AK) is a premalignant lesion that can progress to cSCC over time. AK and cSCC are associated with microbial dysbiosis and an increased abundance of the bacterium Staphylococcus aureus. Although AK and cSCC are highly colonized with S. aureus, a bacterium of the skin microbiota, it is not yet known whether this bacterium is associated with cancer development. Here, we analyze the studies on the relationship between S. aureus and keratinocytic skin neoplasia, evaluating the contribution of S. aureus to the development and prognosis of cSCC and AK lesions. The overabundance of S. aureus and the compounds secreted by this bacterium can induce cancer-promoting changes in skin cells. The presence of high amounts of certain S. aureus strains in premalignant skin lesions may constitute a protumorigenic stimulus by inducing oxidative stress and DNA damage and downregulating DNA repair mechanisms. S. aureus associated with AK and cSCC can trigger keratinocytes to produce inflammatory cytokines typically upregulated in cSCC. These circumstances also suggest a potential specific involvement of S. aureus in the progression from AK to cSCC.